BR-364 in Campo Novo do Parecis, Mato Grosso, Brazil: Impacts of the highway on the urban landscape and active mobility - Lourenço, Vanessa Knutzen; Gulinelli , Érica Lemos; Carignani, Gisele (Technical and Scientific Journal Green Cities, 2025)
Objective – This study aims to diagnose the condition of the BR-364 within the urban perimeter of Campo Novo do Parecis, Mato Grosso, and to analyze the impacts resulting from the barrier effect of this highway on active mobility and the configuration of the urban landscape.Methodology – Adopts a qualitative approach, structured as a case study, in order to understand the complexity of the impacts of the BR-364 on the urban landscape and active mobility in the municipality of Campo Novo do Parecis, Mato Grosso. The methodological procedures encompassed a literature review, documentary research, and fieldwork through on-site visits. Data analysis was conducted using content analysis and information triangulation, complemented by the development of thematic maps and systematization charts of the results.Originality/Relevance – The originality of this research lies in analyzing the impacts of the BR-364 on the urban landscape and active mobility in Campo Novo do Parecis, Mato Grosso - a topic still underexplored in medium-sized cities of the Brazilian Midwest. Its relevance rests in providing insights to support urban planning and mobility management, while offering a methodological framework applicable to other urban contexts intersected by federal highways.Results – The BR-364 plays a dual role: while it connects the region, it also functions as an urban barrier that undermines walkability, safety, and environmental quality. Despite some localized improvements, such as wide sidewalks, significant shortcomings remain, including the absence of bicycle lanes, safe crossings, and adequate tree cover.Theoretical/Methodological Contributions – It contributes by integrating the concepts of barrier effect, active mobility, and urban landscape in medium-sized cities. Methodologically, it employs a qualitative case study approach, combining literature review, documentary research, fieldwork, and content analysis through triangulation. This arrangement, supported by thematic mapping, establishes a replicable model for assessing the impacts of highways in urban contexts.Social and Environmental Contributions – The diagnosis indicates that, in the section studied, the BR-364 simultaneously functions as a regional connectivity axis and as an urban barrier that undermines walkability, the safety of active mobility, and the environmental quality of its surroundings
Keywords: Active Mobility; Urban Landscape; Highway